Small Island Developing States in a post‐pandemic world: Challenges and opportunities for climate action. (23rd February 2022) - Foley, Aideen M.; Moncada, Stefano; Mycoo, Michelle; Nunn, Patrick; Tandrayen‐Ragoobur, Verena; Evans, Christopher
Abstract: Small Island Developing States (SIDS) have been impacted by and responded to COVID‐19 in ways that give us clues about vulnerabilities under climate change, as well as pathways to resilience. Here, we reflect on some of these experiences drawing on case study examples from the Caribbean, Pacific, and Indian Ocean SIDS, exploring how SIDS have responded to COVID‐19 and considering the potential for coping mechanisms enacted for the pandemic to support long‐term resilience to climate change. Island responses to the pandemic highlight both new directions, like tourist schemes that capitalize on the rise of remote working in Barbados and Mauritius, and reliance on tried and tested coping mechanisms, like bartering in Fiji. Some of the actions undertaken to respond to the pressures of the pandemic, such as visa schemes promoting "digital nomadism" and efforts to grow domestic food production, have climate resilience and equity dimensions that must be unpacked if their potential to contribute to more sustainable island futures is to be realized. Importantly, the diversity of contexts and experiences described here illustrates that there is no single "best" pathway to climate‐resilient post‐pandemic futures for SIDS. While the emerging rhetoric of COVID‐19 recovery often speaks of "roadmaps, " we argue that the journey towards a climate‐resilient COVID‐19 recovery for SIDS is likely to involve detours, as solutions emerge through innovation and experiment, and knowledge‐sharing across the wider SIDS community. This article is categorized under: Climate and Development > Sustainability and Human Well‐Being Integrated Assessment of Climate Change > Assessing Climate Change in the Context of Other Issues Abstract : Participants in the Grow Garden initiative, Trinidad and Tobago. Responses to COVID‐19 in Small Island Developing States, such as home gardening to tackle food insecurity, may also support long‐term resilience to climate change, but equity must be centered in decision‐making. Photo courtesy of UNDP Trinidad and Tobago (used with permission).